Beyond the Art of Finger Dexterity: Reassessing Carl Czerny - Gramit, David (Rochester University of Rochester Press, 2008)
Within the history of European music, Carl Czerny (1791-1857) is simultaneously all too familiar and virtually invisible. During his lifetime, he was a highly successful composer of popular piano music, and his pedagogical works remain fundamental to the training of pianists. But Czerny's reputation in these areas has obscured the remarkable breadth of his activity, and especially his work as a composer of serious music, which recent performances and recordings have shown to hold real musical interest.Beyond "The Art of Finger Dexterity" explores Czerny's multifaceted career and its legacy and provides the first broad assessment of his work as a composer. Prominent North American and European musicians and scholars explore topics including Czerny's life and its context; his autobiographical writings and efforts to promote his teacher, Beethoven; his activity as a pedagogue, both as teacher of Liszt and as the authority held up to innumerable amateur women pianists; his role in shaping performance traditions of classical music; the development of his image during and after his lifetime; and his work in genres including the Mass, the symphony, the string quartet, and the piano fantasy.This is the first English-language book on Czerny, and the broadest survey of his activity in any language.Contributors: George Barth, Otto Biba, Attilio Bottegal, Deanna C. Davis, James Deaville, Ingrid Fuchs, David Gramit, Alice M. Hanson, Anton Kuerti, Marie Sumner Lott, James Parakilas, Michael Saffle, Franz A. J. Szabo, Douglas Townsend, and John Wiebe.
Keywords: Czerny, Carl -- 1791-1857; 19th Century (1801-1900); Music history; Keyboard music